Chemotherapy Improved Prognosis of Mesenchymal Chondrosarcoma with Rare Metastasis to the Pancreas. (30th January 2014) - Tsukamoto, Shinji; Honoki, Kanya; Kido, Akira; Fujii, Hiromasa; Enomoto, Yasunori; Ohbayashi, Chiho; Tanaka, Yasuhito
Abstract : Extraskeletal mesenchymal chondrosarcoma is rare and metastasis to the pancreas is extremely rare, with only four cases reported in the literature. The therapeutic effectiveness of chemotherapy remains uncertain. We report a 39-year-old man with extraskeletal mesenchymal chondrosarcoma of the buttock, who had metastases to the pancreas, bones, and lung. He underwent distal pancreatectomy, resection of the buttock tumor, and chemotherapy. He had a good response to chemotherapy and survived for about 3 years after surgery.